Nanoscale effects and polaronic relaxation in CaCu3Ti 4O12 compounds - Ribeiro, Willian C. [UNESP]; Joanni, Ednan [UNESP]; Savu, Raluca [UNESP]; Bueno, Paulo Roberto [UNESP] (Elsevier, 2011)
In the present communication, by using dielectric spectroscopy measurement, the correlations between Nanosized Barrier Layer Capacitance (NBLC) (Bueno et al. (2009) [7]) and the high frequency polaronic near-Debye dipolar relaxation found in CaCu3Ti4O12 compounds was discussed. The polaronic process was confirmed to be closely associated with the ultrahigh dielectric features of CaCu3Ti4O12 materials and its concomitant dielectric loss. Herein, the shift in relaxation frequency as a function of temperature was used for calculating the activation energy for hopping electronic conduction. The value obtained was 33 meV, an energy whose magnitude is compatible and confirmed the hypothesis of polaronic features for this high frequency dipolar relaxation process. Furthermore, it is shown that the nanosized barrier inferred from the NBLC model has a polaronic feature with dielectric permittivity exiting orthogonally to dielectric loss, a phenomenological pattern that contradicts the normally observed behavior for traditional dielectrics but explain the dielectric and conductivity feature of CaCu3Ti4O12 compounds. © 2010 Elsevier Ltd. All rights reserved.
Keywords: A. CCTO; C. Stacking faults; D. Dielectric relaxation; D. NBLC model; Barrier layers; Dielectric permittivities; Dipolar relaxation; Electronic conduction; High frequency; Nano-sized; Nanoscale effects; Polaronic features; Relaxation frequency; Spectroscopy measurements; Activation energy; Dielectric devices; Dielectric losses; Dielectric relaxation; Electron energy loss spectroscopy; Stacking faults; Dielectric materials